How influenza A virus NS1 impedes transcription of the host cell’s messenger RNAs - Daniel Marc (npj Viruses)
How influenza virus non-structural protein NS1 inhibits the activity of nuclear speckles, these liquid-liquid phase separation complexes that control the transcription and post-transcriptional regulation of cellular genes.